A redescription of Trichosurolaelaps dixous Domrow, 1972 (Acari: Laelapidae), from Trichosurus cunninghami (Marsupialia: Phalangeridae) from southern Australia - Hufschmid, Jasmin; Beveridge, Ian; Handasyde, Kathrine Ann; Spratt, David Michael (Folia parasitologica, 2008)
The adults of Trichosurolaelaps dixous Domrow, 1972 are redescribed from a population of Trichosurus cunninghami Lindenmayer, Dubach et Viggers, 2002 in south-eastern Australia. The nymphal stages are described for the first time. Morphologically, T. dixous is similar to Trichosurolaelaps crassipes Womersley, 1956. Morphological differences between the prefemale deutonymphs and adult females of the two mite species are the presence of a single large ventral spur on tibia I of T. dixous. Males of T. dixous could not be distinguished from T. crassipes morphologically and the idiosomal length of male T. dixous was variable (475-683 microm). Protonymphs of the two mite species differed only in size, with that of T. dixous being larger. Although T. crassipes was prevalent in a sympatric population of Trichosurus vulpecula and has been reported from other populations of T. cunninghami in southern Australia, it was never recovered from the population of T. cunninghami studied.
Keywords: Austrálie; Animals; Australia; stadia vývoje; infestace roztoči; Mite Infestations; mikroskopie elektronová rastrovací; Female; Life Cycle Stages; mužské pohlaví; zvířata; Male; roztoči; Microscopy, Electron, Scanning; Trichosurus; ženské pohlaví; Mites